ZKSCAN5 Activates VEGFC Expression by Recruiting SETD7 to Promote the Lymphangiogenesis, Tumour Growth, and Metastasis of Breast Cancer - Li, Jingtong; Yan, Zhifeng; Ma, Jianli; Chu, Zhong; Li, Huizi; Guo, Jingjing; Zhang, Qingyuan; Zhao, Hui; Li, Ying; Wang, Tao (Frontiers in Oncology, 2022)
The growth of lymphatic vessels (lymphangiogenesis) plays a pivotal role in breast cancer progression and metastasis and the immune response. Vascular endothelial growth factor C (VEGFC) has been demonstrated to accelerate cancer metastasis and modulate the immune system by enhancing lymphangiogenesis. However, it remains largely unclear how transcription factors physically regulate VEGFC expression by interacting with histone-modifying enzymes. Like many histone-modifying enzymes, SETD7 plays a key role in cell proliferation and inhibits tumour cell differentiation. In this study, we identified the role of the transcription factor zinc finger with KRAB and SCAN domains 5 (ZKSCAN5) in interacting with histone methyltransferase SETD7 and mediating VEGFC transcription and tumour lymphangiogenesis. ZKSCAN5 interacts with and recruits SETD7 to the VEGFC promoter. By regulating breast cancer-secreted VEGFC, ZKSCAN5 could induce the tube formation of lymph endothelial cells, which promotes tumour proliferation, migration, and metastasis. Clinically, the expression of ZKSCAN5 was frequently upregulated in patients with breast cancer and positively correlated with the expression of VEGFC and the number of lymphatic microvessels. ZKSCAN5 is a poor prognostic factor for patients with breast cancer. Our results characterise the role of ZKSCAN5 in regulating VEGFC transcription and predict ZKSCAN5 as a breast cancer therapeutic target.